Functional properties of nata biocellulose from coconut water medium - Ang, Kathleen M.; Rumbaoa, Rowena Grace O. (2000., 2000)
ABSTRACT In the development of powdered cellulose, nata de coco of class C quality made from coconut water was utilized. The two hydration procedures employed in the production of nata biocellulose (NBC) powder were freeze drying and oven drying. Nata biocelluose produced from freeze drying was white in color, porous and rigid in structure with a smooth texture. It had moisture content reading of 1.325% and a percent yield of 0.625%. Oven dried cellulose was yellow beige in color and hard uneven texture which was rough in some parts. It exhibited a moisture content reading 0.583% and a percent yield of 0.44%. Due to the better quality of the cellulose produced using freeze dying, this method was employed in the standardization of the production of powdered NBC. The three batches of nata biocellulose produced had a % yield ranging from 0.345% to 0.353% and exhibited a moisture content reading which ranged from 1.42% to 1.79%. Statistical analysis established that there were no significant differences between the three batches of nata biocellulose produced. Functional properties of the produced nata biocellulose powder was compared to that of MCC. Results showed that NBC had a greater ability to bind water and fat as well as to emulsify a given food system. MCC however, was more dispersible compared to nata biocellulose a any given conditions. Electron micrograph of the NBC illustrated that it is composed of dense networks of tangled mass of fibers which have varying width.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Nata de coco; Coconut products